(untitled) (Academia Journal of Medicine, 2026)
Background: Early enamel demineralization is a reversible process, and various remineralizing agents have been introduced to restore mineral loss. Among these, casein phosphopeptide amorphous calcium phosphate (CPP-ACP) and fluoride-based formulations are widely used; however, their comparative efficacy in primary teeth remains an area of interest. Aim: To evaluate and compare the remineralization potential of CPP-ACP paste and sodium fluoride on artificially induced enamel lesions in primary molars. Materials and Methods: This in vitro experimental study was conducted on 30 extracted, caries-free primary molars, randomly allocated into three groups (n = 10 each): Group I received CPP-ACP paste (GC Tooth Mousse®), Group II received sodium fluoride toothpaste (0.165% w/w NaF; 750 ppm fluoride) serving as a positive control, and Group III received normal saline as a negative control. Artificial enamel lesions were created by immersing samples in a demineralizing solution (pH 4.5) for 72 hours. The respective agents were applied for four minutes daily for seven days, with specimens stored in artificial saliva between applications. Surface microhardness (SMH) was assessed using a Vickers microhardness tester at baseline (T0), after demineralization (T1), and after remineralization (T2). Data were analyzed using one-way ANOVA, paired t-tests, and Tukey’s post-hoc tests, with significance set at p < 0.05. Results: A significant reduction in SMH was observed following demineralization in all groups (p < 0.05). Post-remineralization, both CPP-ACP and sodium fluoride groups demonstrated a statistically significant increase in SMH compared to the control group (p < 0.05). CPP-ACP showed a greater improvement in microhardness values compared to sodium fluoride; however, the difference between the two groups was not statistically significant. Conclusion: Both CPP-ACP and sodium fluoride exhibited effective remineralization potential on artificial enamel lesions in primary teeth. CPP-ACP demonstrated a comparatively higher, though not statistically significant, remineralization effect. These findings suggest that CPP-ACP can be considered a promising alternative or adjunct to fluoride therapy in pediatric dental care.